Finite Element Analysis of Contact Behavior in Thick-Walled Cylinders - Mohamed Elrawemi; Ali Aburass; Moamar Hamed (African Journal of Advanced Pure and Applied Sciences, 2026)
Shrink-fit assemblies of dissimilar materials, such as aluminum and steel, are widely used in thick-walled structural components to transfer loads without mechanical fasteners. These assemblies offer advantages in weight reduction, compactness, and manufacturing efficiency. However, accurate prediction of stress distribution in such systems remains challenging, as it depends on internal pressure, interference-induced shrinkage pressure, and cylinder geometry. Classical analytical approaches, including Lamé’s equations and Hertzian contact theory, are insufficient for accurately predicting contact stresses, plastic deformation, and residual stresses when nonlinear material behavior and large deformations become significant. In this study, nonlinear finite element analysis using ABAQUS was conducted to investigate the contact pressure, stress distribution, and plastic deformation in two concentric, open-ended aluminum and steel cylinders subjected to shrink-fit conditions. A preload of 66.5 MN/m² was initially applied and subsequently released to achieve a target interference pressure of 1 MN/m² at the interface between the two cylinders. After unloading, half of the original preload (33.25 MN/m²) was reapplied to investigate stress evolution, residual stress development, and material interaction. The obtained results were then compared with those of a single aluminum cylinder subjected to a preload of 66.5 MN/m².The comparison demonstrates that the compound shrink-fit configuration improves stress distribution and reduces peak stresses. These results provide a framework for designing reliable shrink-fit thick-walled assemblies beyond classical methods.